Embodying a New Meaning of Being At Risk: Living With an Implantable Cardioverter Defibrillator for Arrhythmogenic Right Ventricular Cardiomyopathy. (19th October 2016) - Manuel, April; Brunger, Fern
Arrhythmogenic Right Ventricular Cardiomyopathy/Dysplasia (ARVC/D) is a genetic condition that can cause fatal arrhythmias. The implantable cardioverter defibrillation (ICD) is a primary treatment for ARVC/D. Using a grounded theory approach, this study examines the experiences of 15 individuals living with an ICD. The ability to cope with and adjust to having an ICD is influenced by the acceptance of the ICD as something needed to survive, an understanding of the ICD's function, existing support networks, and ones' ability to manage everyday challenges. Coping well requires reshaping ideas about the meaning of being at risk and understanding how the ICD fits into that changing personal risk narrative. A thorough understanding of the unique needs of individuals with ARVC/D and of the specific factors contributing to the psychosocial distress related to having an ICD (vs. having the disease itself) is needed. Nurses must be prepared to provide ongoing support and education to this population.